2008
DOI: 10.1063/1.2888357
|View full text |Cite
|
Sign up to set email alerts
|

Floating nanodot gate memory fabrication with biomineralized nanodot as charge storage node

Abstract: We have demonstrated floating nanodot gate memory (FNGM) fabrication by utilizing uniform biomineralized cobalt oxide (Co3O4) nanodots (Co-BNDs) which are biochemically synthesized in the vacant cavity of supramolecular protein, ferritin. High-density Co-BND array (>6.5×1011cm−2) formed on Si substrate with 3-nm-thick tunnel SiO2 is embedded in metal-oxide-semiconductor (MOS) stacked structure and used as the floating gate of FNGM. Fabricated Co-BND MOS capacitors and metal-oxide-semiconductor field eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 29 publications
2
75
2
Order By: Relevance
“…The fluctuation may reflect the electron trapping by, or electron emitting from the NPs that surround the CNTs. The hysteresis may reflect formation of conductive paths as a result of Co oxide reduction within NPs [10].…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…The fluctuation may reflect the electron trapping by, or electron emitting from the NPs that surround the CNTs. The hysteresis may reflect formation of conductive paths as a result of Co oxide reduction within NPs [10].…”
Section: 2mentioning
confidence: 99%
“…Synthesis of Co oxide NPs within NHBP-LiDps proteins: Co oxide NPs were synthesised within the NHBP-LiDps proteins because electronic memory functions were observed in the previous reports [8][9][10]. The NHBP-LiDps protein (0.1 mg/ml) was dissolved in 100 mM HEPES-NaOH (pH 8.2) buffer and incubated in the presence of 0.5 mM (NH 4 ) 2 Co(SO 4 ) 2 and 1 mM H 2 O 2 at 50 8C for 15 min.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…37) After the protein was removed by UV=ozone treatment, the NPs were buried in a 17 nm control layer of silicon oxide. [159][160][161][162][163] The Co 3 O 4 NP MOSFET required annealing in forming gas after electrode deposition [ Fig. 8(a)].…”
Section: Apoferritinmentioning
confidence: 99%
“…Note that it is crucial to measure the reference curve for each device for evaluating the C-V curves, because the structural variation between devices causes shifts of reference curves for values around 0.1 V. The hysteresis behavior indicates that both holes and electrons are injected into the nanoclusters from the Au electrode; holes are injected with a positive gate bias, while electrons are injected with a negative gate bias. The flatband voltage shift, corresponding to gate-voltage at a half of maximum capacitance (C max ), 28,[44][45][46] was evaluated instead of that defined as gate-voltage at the maximum in G (conductance)-V curve, because the former matches by 0.1 V with the latter; the latter has been frequently used for estimating flat-band voltage. We have found that the flatband voltage is independent of the sweep rate and frequency (Figs.…”
Section: Aip Advances 8 065002 (2018)mentioning
confidence: 99%